Area Development and Policy, the Greater BRICS and a new world order?. Issue 4 (2nd October 2022) - Dunford, Michael; Liu, Weidong; Pompeani, Christophe
ABSTRACT: The establishment of new international economic, political and financial institutions (BRICS, SCO, BRI, EAEU, New Development Bank, Asian Infrastructure Investment Bank) by emerging economies was associated with a wave of interest in the way their relative growth was reshaping the global order. Most comparisons drew on gross domestic product (GDP) data. A succession of recent crises (Western financial crisis, COVID-19 pandemic, Western sanctions on Russia and the associated disruption of supply chains) has, however, suggested that, in terms of real production of energy and minerals, food and manufactures vital for human survival, emerging economies are far stronger that GDP data suggest. This commentary draws on output, trade and balance of payments data to demonstrate that it is indeed the case, though with significant differences between world regions. Moreover, the establishment of new international trade and payments settlement systems may also see a significant geographical redistribution of services, where Western economies remain for the moment dominant.